(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
The influence of UV-radiation and ammonia on plants’ PSA has been investigated. It has been shown that UV-radiation decreases the absorptive ability of pigment apparatus of plants. The combined influence of UV-radiation and ammonia increases the absorptive ability of leaves and inhibits the electron transfer chain of photosynthetic activity of plants. At the same time decrease of quantity of complex pigments (Chlorophylls a, b and carotenoids) is observed.